A Case of Ochrobactrum intermedium Bacteremia Secondary to Cholangitis With a Literature Review - Kassab, Ihab (Cureus, 2021)
Ochrobactrum species are gram-negative, non-lactose fermenting, aerobic bacilli closely related to Brucella genus. Ochrobactrum intermedium (O. intermedium) is an emergent human pathogen that is difficult to differentiate from other Ochrobactrum species by conventional methods. It is known to infect immunocompromised hosts, has the propensity for abscess formation, and is known for its multidrug resistance. We describe the case of an 84-year-old woman with a background of primary sclerosing cholangitis who presented with fatigue, fever, and syncope. Blood cultures grew O. intermedium. Magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography were consistent with cholangitis. Cultures from the biliary duct confirmed the same microorganism. The patient was successfully treated with minocycline. Although rare, O. intermedium should be considered as a differential diagnosis in patients with biliary and gut pathology, particularly in immunocompromised patients.